FRI0270 Identification of novel dysregulated interferon-inducible non-coding rnas in sjÖgren's syndrome. (12th June 2018) - Means, N.; Ice, J.A.; Adrianto, I.; Stolarczyk, A.M.; Joachims, M.L.; Rasmussen, A.; Guthridge, J.M.; James, J.A.; Scofield, R.H.; Sivils, K.L.; Lessard, C.J.
Abstract : Background: Sjögren's syndrome (SS) is a chronic, heterogeneous disease with hallmark features of auto-inflammation and autoantibody production. Upregulation of type I and II interferon-stimulated genes (ISGs), known as the "Interferon (IFN) Signature" is correlated with anti-Ro titers and has been observed both in the salivary glands and peripheral blood of SS patients. Within the 2 p25.2 genomic interval, the long non-coding RNA (lncRNA) negative regulator of the interferon response ( NRIR ) has been identified as inducible by type I IFN and is responsible for the downregulation of the ISGs CMPK2 and RSAD2[. 1 Objectives: We sought to identify additional unannotated ISGs lncRNAs that are differentially expressed (DE) in SS patients utilising correlated expression of RSAD2 . Methods: We evaluated and compared the transcriptome of anti-Ro(+) patients (n=27) and healthy controls (n=27) using RNA-seq with DE defined as q<0.05 and a fold change (FC) ≥2 or≤0.5. qRT-PCR was used to validate DE with primers specific for each RNA of interest. To understand the biological relevance of these transcripts, we performed in vitro time-course experiments to compare the transcriptional changes of unstimulated cells and cells stimulated with either PMA/ionomycin (PMA/I) or universal type I IFN for 36 hours measuring 7 time points. Results: One of the most overexpressed type I ISGs in the SS Ro(+) is RSAD2 (FC=8.05, p=3.29x10E-07). Because of its role in the type I IFN pathway, pairwise correlation coefficients between all DE transcripts and RSAD2 for SS Ro(+) patients were calculated. In total, we found 223 transcripts exhibiting correlation with RSAD2 expression (Pearson's r>+0.70 or<-0.60), including NRIR (FC=2.72, p=5.87x10E-03) and CMPK2 (FC=2.53, p=3.58x10E-03). Of the 223 transcripts, 14 DE expressed lncRNAs correlated with RSAD2 expression. Several antisense ncRNAs situated nearby to other type I ISGs correlated with RSAD2, including: AC099063.1 (FC=2.51), AC004551.1 (FC=3.35), and AP001610.1 (FC=4.12). We confirmed upregulation of these lncRNAs by qRT-PCR from the independent replication (14 Ro(+) and 36 controls) cohort (p=2.49X10E-02, 8.63 × 10E-06, 1.17 × 10E-04, respectively). Based on the locations of the lncRNAs to type I ISGs, HSB-2 cells were stimulated with PMA/I or universal type I IFN. Using qRT-PCR to measure the protein coding genes MX1, OAS1, and GBP5 along with the lncRNAs, AC099063.1 ( GBP5-AS1 ), AP001610.1 ( MX1-AS1 ), and AC004551.1 ( OAS123-AS1 ) showed coordinated regulation with their protein coding counterparts with both stimuli. Conclusions: Given the importance of the IFN signature to disease pathogenesis in the autoantibody positive patients, it is critical that we better understand how this complex pathway is coordinately regulated. Since one critical function of lncRNAs is to regulate the genome, characterising the mechanisms by which these 14 identified by this study regulate the ISG coordinately could result in new diagnostic and/or therapeutic options. Reference: [1] Kambara H, et al. Nucleic Acids Res2014;42(16):10668–80. Disclosure of Interest: None declared